Clinical and psychological factors affecting sudden death risk in myocardial infarction patients - S. A. Boldueva; A. V. Shabrov; I. A. Leonova; T. Ya. Burak; M. V. Samokhvalova; O. V. Trofimova; E. G. Bykova; A. E. Gimgina (Кардиоваскулярная терапия и профилактика, 1970)
Aim. To assess prognostic value of clinical and psychological factors in regard to sudden cardiac death (SCD) risk in patients after myocardial infarction (MI). Material and methods. In total, 420 patients were examined at Day 10-14 after MI; follow-up period lasted for 1-4 years. General clinical examination, echocardiography, 24-hour electrocardiography (ECG) monitoring, late ventricular potentials (LVP) detection, active orthostatic test (AOT), heart rate variability (HRV) assessment, psychological testing, if necessary – coronary angiography and endocardial electrophysiological examination were performed. Results. In the first post-MI year, SCD incidence was 6,7%. SCD risk was predicted by anterior MI localization, left ventricular (LV) aneurysm, heart failure, pre-syncope in anamnesis, hypotension during AOT, sinus tachycardia, left bundle block, anxiety and depression symptoms, leukocytosis and monocytosis in acute AMI period, alcohol abuse in anamnesis, treatment features (no beta-adrenoblockers; diuretic therapy). In multivariate analysis, the most important clinical factors included previous MI, hypotension in AOT, LV ejection fraction, ventricular arrhythmias by 24-hour ECG monitoring, HRV and LVP assessment data. Conclusion. Due to high SCD rates in MI patients, SCD risk should be assessed as early as during hospitalization, using relevant clinical and psychological parameters. If needed, detailed examination and secondary SCD prevention measures should be performed.